Polymorphisms in VEGF and KDR genes in the development of endometriosis: a systematic review - Cardoso,Jessica Vilarinho (2016)
Abstract Objectives: to review studies that used case-control design to verify the association of polymorphisms in VEGF and KDR genes in the development of endometriosis. Methods: the systematic review selected articles published until September 1, 2015 from PubMed, MEDLINE, BVS, SciELO databases, considering the following key words: endometriosis and ("polymorphism" or "SNP" or "genetic polymorphism") and ("VEGF" OR "Vascular endothelial growth factor" or "VEGFR-2" or "Vascular endothelial growth factor-2" or "KDR" or "Kinase Insert Domain Receptor"). Results: 106 articles were identified, only 11 were eligible. Discrepant results were observed regarding polymorphisms in VEGF gene in the development of endometriosis, which can be explained by methodological differences, sample size, eligible control type, using the unadjusted risk estimates and the heterogeneity of the studied population. Only one study investigated polymorphisms in KDR gene in the development of endometriosis, however it was ineligible for this review. Conclusions: to avoid discrepancy in the results, we suggest that the ideal control group should be formed by fertile women and free of gynecological diseases. Multicentric studies with adequate design, involving different population besides the combined analysis on polymorphisms in VEGF and KDR genes are still necessary to contribute in the understanding of this disease, which are social, clinical and economical problems.